2010
DOI: 10.3922/j.psns.2010.2.012
|View full text |Cite
|
Sign up to set email alerts
|

An examination of synaptic proteins following chronic haloperidol in a rat model of tardive dyskinesia.

Abstract: Tardive dyskinesia (TD) is a late-onset side effect mainly affecting the orofacial region of patients treated chronically with classic antipsychotic drugs such as haloperidol (HAL). The causes of TD remain unknown. We hypothesized that faulty synaptic re-organization might be related to TD-like syndromes and used the vacuous chewing movements (VCM) model in rats to investigate the expression of four synaptic proteins, synaptophysin, syntaxin, spinophilin and PSD-95, in brains of HAL-treated rats. Male Sprague-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(84 reference statements)
2
4
0
Order By: Relevance
“…The discrepancies between our findings and the post-mortem findings in these regions may reflect the fact we measured SV2A binding whilst the post-mortem studies measured other synaptic proteins, or could reflect the fact that our sample was younger and had a shorter illness duration than most of the patients in the postmortem analyses, and/or the influence of post-mortem interval on synaptic protein levels 8 . Our null findings in our preclinical study are in agreement with, and extend, previous preclinical findings in which chronic HAL exposure had no statistically significant effect on synaptophysin protein levels in the rat or nonhuman primate cortex 34,35,43 , by showing HAL did not alter the levels or specific binding of another presynaptic protein, SV2A.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The discrepancies between our findings and the post-mortem findings in these regions may reflect the fact we measured SV2A binding whilst the post-mortem studies measured other synaptic proteins, or could reflect the fact that our sample was younger and had a shorter illness duration than most of the patients in the postmortem analyses, and/or the influence of post-mortem interval on synaptic protein levels 8 . Our null findings in our preclinical study are in agreement with, and extend, previous preclinical findings in which chronic HAL exposure had no statistically significant effect on synaptophysin protein levels in the rat or nonhuman primate cortex 34,35,43 , by showing HAL did not alter the levels or specific binding of another presynaptic protein, SV2A.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the volunteers with schizophrenia in our study had taken antipsychotic drugs longer than this. Whilst the null results in our preclinical study are consistent with those of others examining the effect of HAL on presynaptic protein levels using a similar duration of exposure 34,35,43 , our study was not powered to detect small effects so we cannot exclude the possibility that there is a small effect and/or that a longer duration of antipsychotic drug exposure may affect SV2A protein levels or specific binding. Notwithstanding this, our findings from our clinical and preclinical studies suggest that antipsychotic medication exposure is unlikely to account for the lower [ 11 C]UCB-J binding in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Examinations of synaptic proteins have reported either no change [34], decreases [35] [36] [37] or increases [38][39] [40] [41] in pre-or post-synaptic proteins in the striatum. Examinations of synaptic proteins have reported either no change [34], decreases [35] [36] [37] or increases [38][39] [40] [41] in pre-or post-synaptic proteins in the striatum.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Examinations of synaptic proteins have reported either no change [34], decreases [35] [36] [37] or increases [38][39] [40] [41] in pre-or post-synaptic proteins in the striatum. Studies that use chronic intramuscular HAL depot have generally reported no change in multiple pre-and post-synaptic proteins at the tissue, cellular or synaptosomal levels [34], whereas increases have been reported in studies using daily sub-chronic HAL treatment [45] [40]. Studies that use chronic intramuscular HAL depot have generally reported no change in multiple pre-and post-synaptic proteins at the tissue, cellular or synaptosomal levels [34], whereas increases have been reported in studies using daily sub-chronic HAL treatment [45] [40].…”
Section: Synaptic Plasticitymentioning
confidence: 99%